Hypertensive disorders in pregnancy and maternal and neonatal outcomes in Haiti: the importance of surveillance and data collection - Matthew Bridwell; Endang Handzel; Michelle Hynes; Reginald Jean-Louis; David Fitter; Carol Hogue; Reynold Grand-Pierre; Hedwige Pierre; Bradley Pearce (BMC, 2019)
Abstract Background This study aims to determine reported prevalence of hypertensive disorders in pregnancy (HDP) and maternal and neonatal outcomes associated with these disorders among women delivering at selected hospitals across Haiti. Methods A retrospective review of 8822 singleton deliveries between January 2012 and December 2014 was conducted at four hospitals in separate Departments across Haiti. Researchers examined the proportion of women with reported HDP (hypertension, preeclampsia, eclampsia) and the association between women with HDP and three neonatal outcomes: low birth weight, preterm birth, and stillbirths; and two maternal outcomes: placental abruption and maternal death in Hôpital Albert Schweitzer (HAS). Odds ratios for associations between HDP and perinatal outcomes at HAS were assessed using logistic regression, adjusting for potential confounders. Results Of the 8822 singleton births included in the study, 510 (5.8%) had a reported HDP (including 285 (55.9%) preeclampsia, 119 (23.3%) eclampsia, and 106 (20.8%) hypertension). Prevalence of HDP among each hospital was: HAS (13.5%), Hôpital Immaculée Conception des Cayes (HIC) (3.2%), Fort Liberté (4.3%), and Hôpital Sacré Coeur de Milot (HSC) (3.0%). Among women at HAS with HDP, the adjusted odds of having a low birth weight baby was four times that of women without HDP (aOR 4.17, 95% CI 3.19-5.45), more than three times that for stillbirths (aOR 3.51, 95% CI 2.43-5.06), and five times as likely to result in maternal death (aOR 5.13, 95% CI 1.53-17.25). Among the three types of HDP, eclampsia was associated with the greatest odds of adverse events with five times the odds of having a low birth weight baby (aOR 5.00, 95% CI 2.84-8.79), six times the odds for stillbirths (aOR 6.34, 95% CI 3.40-11.82), and more than twelve times as likely to result in maternal death (aOR 12.70, 95% CI 2.33-69.31). Conclusions A high prevalence of HDP was found among a cohort of Haitian mothers. HDP was associated with higher rates of adverse maternal and neonatal outcomes in HAS, which is comparable to studies of HDP conducted in high-income countries.